Biometric features of the eyes of preterm born babies - Grgić, Zorka S; Oros, Ana; Karadžić, Jelena; Čanadanović, Vladimir; Jovanović, Sandra; Bolinovska, Sofija (Vojnosanitetski pregled, 2017)
Background/Aim. Preterm birth and retinopathy of prematurity (ROP) could affect optical and biometric features of eyes and cause refractive errors. The aim of this study was to compare the ocular axial length, anterior chamber depth and lens thickness changes during the first year in preterm born babies with and without ROP. Methods. This prospective longitudinal study included 87 preterm born babies. The examinations were performed at 3 and 12 months after birth and included fundus examination and measurements of the ocular axial length, anterior chamber depth and lens thickness. Based on the results of fundus examination at 3 months, the subjects were divided into two groups and the measurements of those with and without ROP were compared. Results. At 3 months 60.92% of infants had ROP. The mean values in the ROP group were: axial length 16.56 mm and 16.53 mm, chamber depth 2.34 mm and 2.38 mm and lens thickness 4.04 mm and 3.96 mm, in the right and the left eye, respectively. In the no ROP group these values were: axial length 17.06 mm and 17.08 mm, chamber depth 2.31mm and 2.39 mm and lens thickness 4.16 mm and 4.14 mm in the right and the left eye, respectively. At 12 months 28.74% of the children had a change in the ocular fundus as a result of the ROP therapy. In the ROP group the axial length was 19.94 mm in both eyes, chamber depth 3.01 mm and 2.99 mm and lens thickness 4.28 mm and 4.29 mm, in the right and the left eye, respectively. In the no ROP group the axial length was 20.64 mm and 20.29 mm, lens thickness 4.37 mm and 4.36 mm, in the right and the left eye, respectively and chamber depth 3.10 mm in both eyes. Conclusion. In the group of children with ROP axial length of the eye at 3 and 12 months was statistically significantly smaller in comparison to the group without ROP. Statistically significant difference was not found between these groups in the anterior chamber depth and lens thickness